The Emerging Fusarium graminearum NA3 Population Produces High Levels of Mycotoxins in Wheat and Barley - Nicholas A. Rhoades; Susan P. McCormick; Martha M. Vaughan; Guixia Hao (Toxins, 2024)
Fusarium graminearum (Fg) is the primary causal agent of Fusarium head blight (FHB) in wheat, barley, and other small grains in North America and worldwide. FHB results in yield reduction and contaminates grain with mycotoxins that pose threats to human and livestock health. Three genetically distinct North American (NA) populations of Fg have been characterized, which are generally associated with differences in their predominant trichothecene chemotype: NA1/15-acetyl-deoxynivalenol (15-ADON), NA2/3-acetyl-deoxynivalenol (3-ADON), and NA3/3α-acetoxy, 7,15-dihydroxy-12,13-epoxytrichothec-9-ene (NX-2). Recent studies found that the NA3 population had significantly less spread on point-inoculated wheat spikes than the NA1 and NA2 populations, and NX toxins are important for Fg spread and initial infection in wheat. In this follow-up study, to compare the effect of the three populations on initial infection and mycotoxin production on different hosts, we dip-inoculated spikes of the moderately resistant wheat cultivar Alsen and the susceptible barley cultivar Voyager using five strains from each population to evaluate disease, trichothecene mycotoxin accumulation, and trichothecene production per unit of fungal biomass. In dip-inoculated wheat spikes, the NA3 population produced significantly more trichothecene per unit of fungal biomass and accumulated higher levels of trichothecene per plant biomass than the NA1 and NA2 populations, regardless of the disease levels caused by the three populations. In contrast to its critical role during wheat infection, NX toxins had no effect on barley infection. In dip-inoculated barley, the NA1 population was more infectious and caused more severe FHB symptoms than the NA2 and NA3 populations; however, the NA3 population produced significantly higher toxin per unit of fungal biomass in infected barley tissues than the NA1 population. This study provides critical information on the emerging NA3 population, which produces high levels of NX toxin and poses a potential food safety concern.